Relation between the germination and infection ratio on Sida hermaphrodita L. Rusby seeds under hot water treatment - Kurucz, E.; Szarvas, P.; Fári, M. G. (International Journal of Horticultural Science, 2013)
Sida hermephrodita or virginia mallow is a perspective perennial herb in the Malvaceae family able to yield a biomass crop through between ten and twenty years. Additionally, the plants have a lot of uses and benefits for instance it can use it as a fodder crop, honey crop, ornamental plant in public gardens. It has favorable features like fast growing and resistance against the disease and climatic fluctuations, etc. Sida is in base stage of domestication therefore has a serious disadvantage the low and slow germination as a big part of wild plants. Due to the expressly low germination percent the need of seed showing of driller is should tenfold, 200 thousand seed/acre instead of 10-20 thousand what is not available and expensive Therefore practical purposes of our research of seed physiology was to increase the seed germination percent in a disposable ,basically wild Sida population. We examined two factors relating to seed germination percent and seed germination power during our research: the influence of hot water treatment and the effect of exogenus or endogenus infection of seed. However, in our germination tests, utilizing scarified seeds with hot water (65, 80 and 95 oC), 29,33 to 46% germinated of the seeds collected from the population of S. hermaphrodita in Debrecen. The average germination for all season was 5-10 % wihitout treatment and rised using hot water up to almost 50%. When physically scarified used, the oldest seeds showed the best germination (46 %) after the hot water operation in spite of the previus studys (Spooner 1985; Chudik et al. 2010; Doliński R. 2009.). We discovered that there are a distinguished close relationship between the seeds collecting time and the infection, as well as germination percentage. Thus, 2009 season was the most favourable in case of contamination (control:17,33 and 80 oC treatment:0%) as well as germination percent. It could be concluded that, the best season for our findings was 2009 due to autumn harvest of Sida seeds. In our oppinion, the autumn harvesting should be the best time to overcome the problem of the low germination and high infection percentage.